Persepsi Tingkat Kepuasan Penghuni Terhadap Atribut Rumah Susun Sewa Kemayoran - Seriadi, Harri A (Jurnal Sosial Ekonomi Pekerjaan Umum, 2014)
The development of rental public housing program performed to fulfill housing needs for middle and low income people did not always satisfy the renters. Some cases of dissatisfaction found in a number of rental public housing, including in study location, due to incomplete or not fulfilled public housing attributes by its responsible party, management or the government. In general, this research was conducted to understand satisfactory level living in rental public housing by using ?voluntary moving? indicator, and the specific purpose is to measure tenant?s satisfactory perceptual level on seven public housing attributes which conceptually influenced living satisfaction. In scientific literature, there is a relation between tenant?s satisfactory perceptual level and the fulfillment of public housing attributes. Conceptually, this research used psychology concept and cognitive approach with quantitative design. Research location was conducted at Kemayoran rental public housing, and survey was used as a primary tool to collect data. Additional data obtained from report published by Kemayoran Rental Housing Management, technical report, official publication, literature review and visual observation. The research result revealed that in general living in Kemayoran rental public housing generally fit into category satisfactory level, and in particular three out of seven public housing attributes, according to majority of respondent opinion, was ?least satisfied? and the remaining attributes are ?not satisfied?. Due to the dynamic of satisfaction measurement, additional research to determine factors which influenced perceptual level of respondent and empirical level of attributes is advisable.